Seasonal labour migration in rural Nepal: a preliminary overview. - Gill,Gerard J. (2003)
SUMMARY: One of the aims of the Rural Livelihoods Futures study is the development of appropriate rapid appraisal methods. This is particularly important in areas like seasonal labour migration which are known to be important to rural livelihoods, yet where understanding is particularly scant. A survey was conducted using as key informants a panel of postgraduate students in Nepal. Most of the respondents were agricultural extension officers. The purpose was (a) to test the methodology, and if the results were encouraging (b) to use the data to gain an overview of migration patterns and dynamics and how they fit within a broader livelihoods framework. The data validation exercise produced encouraging results. Seasonal migration in Nepal results from both push (high levels of poverty and food insecurity) and pull factors (seasonal employment opportunities elsewhere). The survey shows very complex patterns, with flows mainly going from higher to lower altitudes within Nepal and to better developed areas in India. Agricultural work seems to dominate, but there are important flows for non-agricultural work and some for NTFPs. Many of these flows are of recent origin. Daily wage rates are very variable, but generally lie in the US$1.503.00 range. Wage rates in India are significantly higher than in Nepal, non-agricultural wages are higher than those in agriculture, and wage rates for recent flows are higher than for traditional ones. However the picture here is complicated by the provision of food by some employers but not others. Migration has been an increasing phenomenon, with both push and pull factors on the rise. New opportunities in areas like horticulture, dairying and poultry have been arising faster than traditional ones have been disappearing. New opportunities are also coming up in agro-industry, NTFPs and the non-agricultural sector. Tragically, the present insurgency situation has reversed this trend. Livelihood opportunities across a spectrum of activities are diminishing or even disappearing, and the food security situation is steadily worsening both because of actions of the insurgents and by reason of official measures taken to curb them. A recent study of rural livelihoods and food security issues throws important light on the issue of seasonal migration from a micro perspective. This indicates that in the poorest villages seasonal migration is the main livelihood source for the poor households. Migration is also an increasing phenomenon, with migrants staying away longer. Even in the more prosperous Terai, push factors drive the lowest castes to migrate. However, other evidence indicates that outside of the lowest caste migration makes a positive contribution to Terai livelihoods, with the pull of new livelihood opportunities offering a promising route out of poverty. In conclusion, seasonal labour migration is too important a topic for policy makers to continue to overlook. The present survey has added to the store of knowledge on seasonal labour migration at the macro level, complementing existing village level studies, but much more needs to be done before concrete new policy measures could be recommended. A fully-resourced study therefore needs to be conducted if the dimensions and dynamics of this important issue are to be properly understood. A first imperative would be to repeat the present study with a larger number of informants. The key informant base should go beyond the public sector and bring in representatives of NGOs and the commercial private sector. It is also imperative to gain a clear picture of the numbers involved in seasonal migration, and this would require working with migrants themselves, using a participatory approach. The micro work already done, together with the findings of the present survey, will be invaluable in guiding this future work.